Socioeconomic Status of Nepalese Employed Women in institutional Sector: A Sociological Study of Dharan Sub-Metropolitan City - Sharma, Bigyan; Verma, Rakhi (Dristikon: A Multidisciplinary Journal, 2021)
Gender role has been changing in Nepali society. Traditional rigid patriarchal system has been changing gradually. Particularly urban society has realized such change. Women have marched towards the breadwinning job which was assumed to be the job of male member in traditional society. This research article is dedicated to the understanding of the condition of dual role of working women and increasing socioeconomic status of urban society. This article is based on the primary data. Online questionnaire has been used as the main tool for data collection. Obtained data were analyzed by using the SPSS program. Result of this study shows that there is the situation of double burden of household chores and income generating work of outer periphery. They are facing different physical, mental, social difficulties in both sectors’ work. However, their socioeconomic status has been changing positively in society along with the changing gender role in the urban society.